The physiological polyphosphate as a healing biomaterial for chronic wounds: Crucial roles of its antibacterial and unique metabolic energy supplying properties. (1st February 2023) - Müller, Werner E.G.; Schepler, Hadrian; Neufurth, Meik; Wang, Shunfeng; Ferrucci, Veronica; Zollo, Massimo; Tan, Rongwei; Schröder, Heinz C.; Wang, Xiaohong
Highlights: Wound healing, especially the healing of chronic wounds, requires an increased demand for metabolic energy (ATP). The physiological polymer polyphosphate (polyP) is an efficient source for the generation of ATP during wound regeneration. In addition, polyP undergoes coacervation, a process during which bacteria are killed. These two pillars are the basis for the successful regeneration of chronic wounds in humans. Abstract: Insufficient metabolic energy, in the form of adenosine triphosphate (ATP), and bacterial infections are among the main causes for the development of chronic wounds. Previously we showed that the physiological inorganic polymer polyphosphate (polyP) massively accelerates wound healing both in animals (diabetic mice) and, when incorporated into mats, in patients with chronic wounds. Here, we focused on a hydrogel-based gel formulation, supplemented with both soluble sodium polyP (Na-polyP) and amorphous calcium polyP nanoparticles (Ca-polyP-NP). Exposure of human epidermal keratinocytes to the gel caused a significant increase in extracellular ATP level, an effect that was even enhanced when Na-polyP was combined with Ca-polyP-NP. Furthermore, it is shown that the added polyP in the gel is converted into a coacervate, leading to encapsulation and killing of bacteria. The data on human chronic wounds showed that the administration of hydrogel leads to the complete closure of these wounds. Histological analysis of biopsies showed an increased granulation of the wounds and an enhanced microvessel formation. The results indicate that the polyP hydrogel, due to its properties to entrap bacteria and generate metabolic energy, is a very promising formulation for a new therapy for chronic wounds.